2009
DOI: 10.1080/00016350802714726
|View full text |Cite
|
Sign up to set email alerts
|

The human periodontal membrane – focusing on the spatial interrelation between the epithelial layer of Malassez, fibers, and innervation

Abstract: It is suggested that the genetic composition of the epithelial layer of Malassez in the periodontal membrane may be the key to understanding the different functions of the periodontal membrane and also the individual differences of these functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These observations indicate that innervation is not only important for early tooth formation (6, 7) but also for eruption. As innervation has recently been observed in the close proximity of the root surface (10), it is suggested that the innervation plays a role not only in the onset of tooth formation and for the eruption process but also for the ongoing root formation or maturation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that innervation is not only important for early tooth formation (6, 7) but also for eruption. As innervation has recently been observed in the close proximity of the root surface (10), it is suggested that the innervation plays a role not only in the onset of tooth formation and for the eruption process but also for the ongoing root formation or maturation.…”
Section: Discussionmentioning
confidence: 99%
“…39 A close association between ERM and nerve fibers in the PDL space has been demonstrated in several species. 35 -38,40 -42 It has been shown that experimental transection of the inferior alveolar nerve in rats not only reduced the distribution and size of ERM cell clusters but also resulted in dentoalveolar ankylosis. 43…”
Section: Morphologymentioning
confidence: 99%
“…D marks the dentin. Left: normally developed root surface (brown nerve cells) [89, 103]. Right: two sections of tooth root surfaces from teeth extracted due to arrested eruption.…”
Section: Figurementioning
confidence: 99%